2021
DOI: 10.31880/10344/10228
|View full text |Cite
|
Sign up to set email alerts
|

The Amsterdam Doughnut: moving towards “strong sustainable consumption” policy?

Abstract: Scholars in sustainable consumption increasingly highlight the limitations of "weak sustainable consumption" approaches to overcome the challenges of the current environmental crisis. While efforts to enable cleaner production and circular flows of materials are necessary and important, progress in environmental efficiency tends to deviate attention away from a more critical challenge: advancing sufficiency. In order to deliver "absolute" improvements, reducing production and consumption levels (an explicit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Our findings for Amsterdam are largely in line with those of previous research in the area. For instance, Maldini (2021), found that, while Amsterdam Circular 2020-2025 Strategy's discourse is quite holistic and progressive, its implementation is "incipient and limited" as it does not include any explicit measures and targets to reduce citizens' overconsumption in a socially equitable manner. Cramer (2020aCramer ( , 2020b) analysed Amsterdam's previous CE programme (implemented from 2015 to 2019), concluding that it only brings about preliminary progress towards CE as it fails to challenge sector behaviours or product chains.…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings for Amsterdam are largely in line with those of previous research in the area. For instance, Maldini (2021), found that, while Amsterdam Circular 2020-2025 Strategy's discourse is quite holistic and progressive, its implementation is "incipient and limited" as it does not include any explicit measures and targets to reduce citizens' overconsumption in a socially equitable manner. Cramer (2020aCramer ( , 2020b) analysed Amsterdam's previous CE programme (implemented from 2015 to 2019), concluding that it only brings about preliminary progress towards CE as it fails to challenge sector behaviours or product chains.…”
Section: Comparative Analysismentioning
confidence: 99%
“…The policies of these cities thus don't live up to the socially progressive vision they set for themselves. Amsterdam is often presented as a pioneer and an example of best practice in the urban CE transition and Circular Glasgow was a finalist of the Circulars Award of the World Economic Forum (Cuomo et al, 2020;Maldini, 2021;Williams, 2021). Both cities have thus built up a strong reputation as CE innovators which further enhances the competitiveness of their CE business sector while taking limited tangible actions to fundamentally transform their production and consumption systems.…”
Section: Social Justice and Transformationmentioning
confidence: 99%